Petrology and Olivine Fabric of Lodranite NWA 2235 - Yasutake, Masahiro; Yamaguchi, Akira (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Tue. 4 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object